2019
DOI: 10.1111/acel.13054
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PKA/SIRT1 signaling pathway by photobiomodulation therapy reduces Aβ levels in Alzheimer's disease models

Abstract: A hallmark of Alzheimer's disease (AD) is the accumulation of amyloid‐β (Aβ), which correlates significantly with progressive cognitive deficits. Although photobiomodulation therapy (PBMT), as a novel noninvasive physiotherapy strategy, has been proposed to improve neuronal survival, decrease neuron loss, ameliorate dendritic atrophy, and provide overall AD improvement, it remains unknown whether and how this neuroprotective process affects Aβ levels. Here, we report that PBMT reduced Aβ production and plaque … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(139 citation statements)
references
References 41 publications
5
134
0
Order By: Relevance
“…Aβ, the main component of amyloid plaques, was shown to play a crucial role in the development of AD pathologies [51]. Recent study reported that excessive Aβ generation and deposition could change cell metabolism and trigger Tau hyperphosphorylation, synaptic dysfunction, oxidative stress and neuroin ammation, further leading to progressive recognition dysfunction [1]. Aβ is produced by sequential cleavage of β-and γ-secretases at the C terminus of amyloid precursor protein (APP) [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aβ, the main component of amyloid plaques, was shown to play a crucial role in the development of AD pathologies [51]. Recent study reported that excessive Aβ generation and deposition could change cell metabolism and trigger Tau hyperphosphorylation, synaptic dysfunction, oxidative stress and neuroin ammation, further leading to progressive recognition dysfunction [1]. Aβ is produced by sequential cleavage of β-and γ-secretases at the C terminus of amyloid precursor protein (APP) [51].…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is a neurodegenerative disease characterized by progressive memory loss and cognitive decline. Clinically, the main pathological features of AD are the extracellular accumulation of senile plaques comprised of amyloid-beta (Aβ) peptides, intracellular neuro brillary tangle composed of highly phosphorylated Tau (p-Tau) and neurodegenerative changes accompanied by synaptic dysfunction and neuronal damage [1]. Currently, the pathogenesis of AD is still not completely understood.…”
mentioning
confidence: 99%
“…In addition to activating CREB [74][75][76][77][78][79], which induces PGC1␣ transcription [83,91], both cAMP/PKA and cGMP/PKG signaling activate SIRT1 [94-96, 98, 104-110]. SIRT1 exerts multiple beneficial effects in AD, including downregulating pro-amyloidogenic ␤-secretase (BACE1) and upregulating anti-amyloidogenic A Disintegrin and metalloproteinase domain-containing protein 10 (ADAM10) [106], as well as deacetylating and thereby post-translationally activating PGC1␣ [97,[111][112][113][114][115][116][117][118].…”
Section: Camp Cgmp Sirt1 and Pgc1αmentioning
confidence: 99%
“…PBM is known to activate multiple pathways such as ERK/ CREB (Meng et al 2013;Gu et al 2017;Heo et al 2019), cAMP/PKA/SIRT1 (Zhang et al 2020), PKC (Zhang et al 2008), Src/Syk/PI3K/Akt (Song et al 2012), and Akt/ GSK3β/β-catenin (Liang et al 2012), involved in various molecular networks in the cellular system. From the data, three significant paths through which the above-mentioned signaling cascades might be activated after PBM by CCO stimulation could be identified as follows:…”
Section: Mitochondrial Stimulation Triggers Several Signaling Pathwaysmentioning
confidence: 99%
“…Drp1-S616 (serine 616) phosphorylation (fission promoting) was repressed, and Drp1-S637 (serine 637) phosphorylation (fusion promoting) was supported, Drp1-Fis1/Mff interactions were prevented, and expression and localization of the other fission proteins OPA1 and MFN1 were attenuated by irradiation, allowing the preservation of mitochondrial integrity (Wong-Riley et al 2005;De Taboada et al 2011;Purushothuman et al 2014;Huang et al 2014;Lu et al 2017;Zhang et al 2020). SIRT1, activated by PBM (Zhang et al 2020), is also previously known to support mitochondrial biogenesis (Xu et al 2018;Zhou et al 2018). Hence, improvement in mitochondrial health through PBM therapy could also be through this mechanism.…”
Section: Antioxidant Capacity and Mitochondrial Preservationmentioning
confidence: 99%